Competenze e formazione STEM come motore della competitività: l’esperienza di Federchimica, federazione nazionale dell’industria chimica - Federchimica (Chimica nella Scuola, 2024)
The chemical industry, together with the chemical science, plays a fundamental role in sustainable development and in the quality of our lives. All the chemical companies are constantly looking for young people, high school and university graduates. For this reason, Federchimica, the Italian federation of the chemical industry, organizes every year dissemination and orientation initiatives for all school cycles, from Primary School to University, with the aim of integrating and expanding school curricula. We work in synergy with all Education stakeholders: the Ministry of education supports our projects and disseminates them, member companies open the doors of their factories describing the value of their products and showing their attention to sustainability, sector and local Associations create events dedicated to dissemination and orientation.